2007
DOI: 10.1080/17453670610013420
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow and microdialysis in the human femoral head

Abstract: BackgroundIf it would be possible to detect lack of flow and/or the development of ischemia in bone, we might have a way of predicting whether a broken bone will heal. We established microdialysis (MD) and laser Doppler (LD) flow measurement in the human femoral head in order to be able to detect ischemia and measure changes in blood flow.Material and methods In 9 patients undergoing total hip arthroplasty for primary osteoarthrosis, two MD catheters were inserted into the femoral head through two drill holes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 20 publications
2
23
1
Order By: Relevance
“…Compared with the study done on human femoral heads (Bøgehøj et al 2007), where the glycerol concentration increased over the sample period as the bone became more and more ischemic, we did not find any signs of cell damage in the in-vivo drill hole study. This suggests that the measurements from the in-vivo study were from the bone and not just from a shell of damaged bone around the drill canal.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…Compared with the study done on human femoral heads (Bøgehøj et al 2007), where the glycerol concentration increased over the sample period as the bone became more and more ischemic, we did not find any signs of cell damage in the in-vivo drill hole study. This suggests that the measurements from the in-vivo study were from the bone and not just from a shell of damaged bone around the drill canal.…”
Section: Discussioncontrasting
confidence: 94%
“…A relative recovery of 57% is in accordance with the results obtained in our study on human femoral heads (Bøgehøj et al 2007). The rather low RR compared to other studies (Rooyackers et al 2004), where almost complete recovery has been reported, is most likely due to the high flow rate of 2 μL/min.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations